2020
DOI: 10.7150/ijms.40131
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer therapeutic benefit of red guava extracts as a potential therapy in combination with doxorubicin or targeted therapy for triple-negative breast cancer cells

Abstract: Guava extracts purified from leaf and bark have many bio-active molecules with anti-cancer activities. In addition, lycopene-rich extracts obtained from red guava fruit can induce apoptosis in estrogen receptor−positive breast cancers. Triple-negative breast cancer (TNBC) lacks estrogen receptors, progesterone receptors and human epidermal growth factor receptor 2 (HER2) and, therefore, hormone therapy and targeted therapy are not used in the clinic. The purpose of this study was to determine whether red guava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…19 Additionally, cleaved PARP can also be upregulated during the cell apoptosis. 20,21 Our finding was consistent with these studies, suggesting that knockdown of MAGOH or double knockdown of MAGOH and MAGOHB induced the apoptosis of gastric cancer cells via upregulation of cleaved caspase 3 and cleaved PARP. Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution.…”
Section: Discussionsupporting
confidence: 90%
“…19 Additionally, cleaved PARP can also be upregulated during the cell apoptosis. 20,21 Our finding was consistent with these studies, suggesting that knockdown of MAGOH or double knockdown of MAGOH and MAGOHB induced the apoptosis of gastric cancer cells via upregulation of cleaved caspase 3 and cleaved PARP. Cyclin B1, CDK1 and p27 Kip1 were key mediators in cell cycle distribution.…”
Section: Discussionsupporting
confidence: 90%
“…Nowadays, more and more agents from natural products have been used to treat cancer based on combination therapy [ 10 ], such as red guava extracts, which could promote doxorubicin-, tarceva-, and iressa-induced cytotoxicity in triple-negative breast cancer through modulating apoptotic or necrotic cell death pathways [ 11 ]. Ursolic acid (UA) ( Figure 1 A), a pentacyclic triterpene, is a common chemical constituent existing mainly in the Lamiaceae family [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al studied the anticancer activity of two extract types from red guava fruit, total extracts, and smaller molecular weight (< 30 kDa) extracts (LMW extracts). [85] They both induced apoptosis in MDA-MB-468 cells, while they induced a higher percentage of dead cells as a result of the necrotic death pathway rather than the apoptotic death pathway in MDA-MB-231cells, which activate the caspase-3/PARP signaling pathway to induce cytotoxicity. Besides, when the extracts were combined with the doxorubicin, Tarceva or Iressa, the anti-cancer activities were significantly increased in MDA-MB-231 and MDA-MB-468 cells, which suggested that they both promote chemotherapy-and targeted therapy-induced anticancer activities.…”
Section: Natural Extracts With Anti-tnbc Activitiesmentioning
confidence: 97%
“…The lycopene‐rich extracts obtained from red guava fruit can induce apoptosis in estrogen receptor‐positive breast cancers. Yu et al studied the anticancer activity of two extract types from red guava fruit, total extracts, and smaller molecular weight (<30 kDa) extracts (LMW extracts) [85] . They both induced apoptosis in MDA‐MB‐468 cells, while they induced a higher percentage of dead cells as a result of the necrotic death pathway rather than the apoptotic death pathway in MDA‐MB‐231cells, which activate the caspase‐3/PARP signaling pathway to induce cytotoxicity.…”
Section: Natural Extracts With Anti‐tnbc Activitiesmentioning
confidence: 99%